Understanding personality disorders - Krolewicz, Christine (Diseases and disorders series., 2020)
Explains the causes and treatments of various personality disorders, and discusses how people cope with them. Also details ways to support someone with these disorders. Includes primary and secondary source quotations, annotated bibliographies, color photographs, a glossary, and organizations to contact for additional information.